Pengaruh Layanan Bimbingan dan Konseling Dengan Prestasi Belajar Siswa SMA - Hanwar Priyo Handoko (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2017)
The problem in this research is the learning service in guidance and counseling is good enough, but the student's learning achievement is quite even less good. This type of research is quantitative, then the population is high school students. This study aims to find out the learning service in guidance and counseling by teacher guidance and konsleing on the students. And to know is there any relation between learning service in guidance and counseling with learning achievement. The conclusion of this research is there is relation between service learning in guidance and counseling with high school student achievement. The results show that ???? count greater than ???? table at 5% significant level is 0.361 and the significant level of 1% is 0.463, or 0.463 <0.603> 0.361.